Strategi dan Media Pembelajaran Pendidikan Agama Islam di Era Pandemi Covid-19 - Mardianto, Mardianto; Anas, Nirwana; Baniah, Sri; Sadat, M. Anwar (Sekolah Tinggi Agam Islam Sumatera Medan, 2021)
Strategy and media are important components in the learning process. In the era of the covid-19 pandemic, various strategies and learning media that have been used by teachers, do not seem to be able to play more roles through online learning. This is due to the design of learning strategies and media that have been intended face-to-face (offline, offline). This paper aims to analyze the appropriate strategies and media used in learning Islamic religious education (PAI) in the covid-19 era. This research uses a qualitative approach with a literature study method. Analyze and test the validity of the data using reference materials, including scientific articles, books, proceedings and final assignments (thesis, thesis, dissertation). The results of this study indicate that (1) the appropriate strategy used is distance learning strategy (PJJ). This is based on the stipulation of social distancing policies by the government towards the Indonesian people, including in the field of education; and (2) the right media to use is an online application in the form of WhatsApp Group, Google Classroom, E-Learning, Youtube, Google Meeting and Zoom.